Specifics of temperature extremes under the conditions of urban climate - STŘEDOVÁ, Hana; FUKALOVÁ, Petra; ROŽNOVSKÝ, Jaroslav (Contributions to Geophysics and Geodesy, 2010)
Urban climate causes intensive physical stress with negative impacts on health.One of the main risk factors is incidence of long-term period of high temperatures duringthe summer months, so-called heat waves. As a heat wave, a period of at least 3consecutive days with maximum daily air temperature ≥ 30 °C was considered. In thispaper the heat-wave incidence and its dynamics are defined in the long-term monitoringin the cadastral of Brno. To determine the impact of urban heat island on observedcharacteristics, the temperature data series directly affecting the urban environment andtemperature data series of non-urban area were evaluated. Urban climate is representedby Brno-Zabovresky station, and sub-urban climate by Brno-Turany station. Resultsare presented for the longest possible period, i.e. since 1987 when measurements inZabovresky began till 2008 (22 years). For the evaluation, the homogenized data of dailymaximum air temperature was used. The basis of the data was obtained by measurementat CHMI station network. The longest average length of the heat wave was recorded in1994 (Zabovresky and Turany 8 days). The longest maximum length of the heat wavewas recorded in 1994 (Zabovresky 19 days, Turany 17 days). The maximum number ofheat waves per year was 6 at the station Brno-Zabovresky and 4 at Turany (1992, 1998 –Zabovresky and 2003 – Turany). The results showed significant specifics of urban climateas compared to suburban areas.